Auk Nr8 . Pit No. 8 - Kaat, Marianna (Kaat, Marianna ; Fetisova, Olena, 2010)
Verzio9 FF Submission. Duration: 01:35:00 Snizhne, once a flourishing Ukrainian mining town, is plagued today by crushing poverty. For years, the town's desperate residents have been illegally mining coal on their own, dangerously excavating abandoned mines, the basements of condemned buildings, the nearby woods, and even their own backyards. Everyone digs to survive – women, pensioners, unemployed miners, even children. After leaving his alcoholic mother's home, 15-year-old Yura has put his schooling and his dream of becoming a cook on hold. He takes it upon himself to provide for his sisters the only way he knows: by working the illegal pits. In the absence of adults, Yura shoulders family responsibilities – parenting, shopping, cooking meals, and making ends meet. A heart-rending story of children forced to grow up too quickly with no role models.